2017
DOI: 10.5296/ijl.v9i5.11792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Listening Comprehension Anxiety from Saudi EFL Learners’ Perspectives

Abstract: Anxiety has been an important topic of discussion in foreign language learning. Listening comprehension anxiety can have negative effects on learners' performance. Therefore, this paper aims at exploring the effects of listening comprehension anxiety on Saudi English as a Foreign Language (EFL) learners at Majmaah University, Saudi Arabia. This qualitative case study research design involves 15 participants. The findings show that the learners experienced high level of listening comprehension anxiety in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In general, all these theories lead to motivate learners from external interest to internal interest. Expectancy-value theory is the expectancy of learners' achievement and quality rather than quantity (doing many tasks in the language class) (Oteir, 2017). Achievement motivation is related to expectancy-value theory.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, all these theories lead to motivate learners from external interest to internal interest. Expectancy-value theory is the expectancy of learners' achievement and quality rather than quantity (doing many tasks in the language class) (Oteir, 2017). Achievement motivation is related to expectancy-value theory.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Their anxiety of listening exercises makes them negative effective on learners' performance and involvement (Oteir, 2017). Therefore, to reduce their anxiety, persuading them with music (English songs with performance) is one of the most effective ways • reducing stress…”
Section: Activities With Short Video Clipmentioning
confidence: 99%
“…5.4; whereas, situation is more appalling in IELTS general category, where average bands are 5.1, i.e., lowest in the world. The past literature also confirms that Saudi EFL students struggle in English listening skills and their performance is below the par (Hamouda, 2013;Mohamed, 2018;Oteir & Aziz, 2017). Therefore, with the aim of attaining insights pertinent to the alarming condition of Saudi students' English listening, it appears unavoidable to conduct an inter-field research concerning constructs that have not been investigated in relation to EFL listening comprehension performance.…”
Section: Introductionmentioning
confidence: 98%
“…First, students are unable to cope with listening classes due to the fast speed of the speech in the audio, unfamiliar words, insufficient knowledge about the listening content, loss of concentration, and difficult accent (Almjlad, 2017). These problems cause depression, distraction, isolation, avoiding listening skill classes, getting a low level of achievement and performance among the students (Oteir and Aziz, 2017). Second, teaching listing is restricted to complete assessment activities without providing sufficient exposure to comprehensible input.…”
Section: Listening In Language Teaching Methodologiesmentioning
confidence: 99%
“…Almjlad (2017) found that lack of prior knowledge regarding the listening topic, loss of concentration, and challenging accents are the toprated problems followed by unfamiliar words and fast speech of the audio. Depression, distraction, isolation, avoiding listening skill classes, getting the low achievement and performance are other some concerned issues in the listening classes in Saudi Arabia (Oteir & Aziz, 2017). The study assumes that matching all or parts of the audio with LT can develop awareness of form-meaning relationships and word recognition skills (Vandergrift, 2007) and can play a significant role in enhancing listening acquisition and listening comprehension.…”
Section: Introductionmentioning
confidence: 99%